Automated Mobile Platform for transporting a Residential Garbage Bin to the Collection Point - Omar Ayman Hamzeh; Judhi Prasetyo (Master Program in Mechanical Engineering, Gunadarma University, 2026)
Waste disposal is a routine yet physically demanding household task. For residents of villas and townhouses, manually transporting garbage bins to roadside collection points presents significant challenges, particularly for elderly and mobility-impaired individuals. Missed scheduled pickups can result in waste overflow. To address this problem, this paper presents the design and evaluation of an autonomous mobile platform prototype capable of transporting a 35-liter trash bin to a collection point and returning within a residential driveway. The prototype utilizes an electric toy car as its base, incorporating an ESP-32 microcontroller, ultrasonic sensors for obstacle detection, infrared (IR) sensors for boundary navigation, and relay modules to actuate a garage door. The system was evaluated over 80 trials. During daytime testing, the final rotational maneuver achieved a 20% full-journey success rate, as intense ambient sunlight frequently overpowered the IR sensors. In contrast, nighttime trials yielded a 65% full-journey success rate, demonstrating improved performance when the sensors were not affected by daylight. These findings indicate that the IR sensors' sensitivity to daylight and the chassis' alignment issues during rotation limited the prototype's reliability, as the chassis struggled to realign with the boundary line after completing a U-turn. In summary, while the prototype demonstrates proof of concept and potential for automated waste transportation, further refinement of the navigational system and rotational maneuver is required for consistent and reliable operation.